Respuesta :

To write the expression log₅4 - log₅6 in a single logarithm, we have to use change of base property and division property of logarithm.

Given that the expression is log₅4 - log₅6.

We are required to tell the name of the property of logarithm which will help us to express the expression in a single logarithm.

Change of base property is property which tells that [tex]log_{a}b=log_{x}b /log_{x}a[/tex].

Division of logarithm says that log(m/n)=log m-log n.

The expression is  log₅4 - log₅6.

log₅4 - log₅6=log 4/log 5-log 6/log 5

=(log 4+log6)/log 5

=log(4*6)/log 5

=log 24/log 5

=log (24-5)

=log 19

Hence to write the expression log₅4 - log₅6 in a single logarithm, we have to use change of base property and division property of logarithm.

Learn more about change of base theorem at https://brainly.com/question/24788069

#SPJ4